Pengaruh Stres Akademik terhadap Kualitas Pola Tidur Mahasiswa - Muhammad Yusuf Gunawan; Naya Naisyia Sahda Aulia; Adystia Milkyna Puteri Gicella; Sri Mulyeni (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
Academic stress, such as the burden of assignments, exam pressure, and the obligation to complete a thesis, can potentially cause various negative impacts, one of which is sleep quality issues. This study aims to examine how academic stress affects students' sleep quality based on empirical findings from various previous studies. The method used was a qualitative approach with a literature study design. Data sources were drawn from national scientific journals and reference books relevant to the topic of academic stress and students' sleep quality. A literature search was conducted through the Google Scholar database, and the collected data were analyzed using content analysis methods to determine the interrelationships between variables, the patterns of relationships found, the trends in the results, and the main conclusions of the studies reviewed. The results of the study showed that the majority of students fell into the medium to high academic stress category and had poor sleep quality. Academic stress was significantly associated with various sleep disorders, including difficulty initiating sleep, insufficient sleep time, and the habit of waking up at night. Physiologically, stress triggers increased activity of the sympathetic nervous system and stress hormones, while psychologically, it causes significant anxiety and rumination that contribute to decreased sleep quality in students. Therefore, it is recommended that students adopt stress management and healthy sleep habits, and that educational institutions provide support programs to improve students' well-being and quality of life.